Origin and distribution of surface sediments in the Grgur Channel, Adriatic Sea, Croatia - Pikelj, Kristina (Array, 2009)
Summary: Granulometrical, mineralogical and morphological investigation of the sea-bottom sediments in the Grgur Channel revealed five sediment types; the most frequent of them are muds containing some amount of coarse sediment fractions (sand and gravel). The coarsest fractions are prevalently composed of recent shell fragments. Unexpected well rounded carbonate gravel was found SE of the Prvić Island at 83 m of water depth. This gravel was presumably transported, shaped and deposited during a lowstanding sea-level by stream and/or in beach environment. Fine-grained fractions have siliciclastic composition and show a prevalenty terrigenous origin. One part of the fine-grained fraction originates from recent subaerial weathering of flysch outcrops and the other from subaerial erosion of presently submerged flysch outcrops active during a lower sea-level. Due to the rapid Late Pleistocene-Holocene transgression, the investigated sediments are now below the present wave-base. Due to the presumed very low or even negligible recent sedimentation in the study area, older sediments in the Grgur Channel remain uncovered and mixed by burrowing organisms. Therefore, analyzed surface sediments from the Grgur Channel are considered as a mixture of recent and subrecent deposits. By this investigation, a new seabed sediments map of the Grgur Channel was produced, as an improvement of the existing sedimentological map of the Kvarner area